Predictor of Percutaneous Radio-Frequency Rhizotomy Outcomes for Trigeminal Neuralgia: A Single Center Prospective Cohort Study - Mustaqim Prasetya; Aji Wahyu Wardhana; Peter Adidharma; Rezka Fadillah Yefri; Adi Sulistyanto; Fadhil Fadhil; Selfy Oswari; Ryan Rhiveldi Keswani; Muhammad Kusdiansah; Yunus K. Aji; Abrar Arham (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2026)
Background: Percutaneous radiofrequency rhizotomy (PRFR) offers a minimally invasive alternative for trigeminal neuralgia (TN) patients who are ineligible for microvascular decompression (MVD) or who suffer from refractory TN following MVD. However, clinical outcome predictors for PRFR, particularly in low-to-middle-income countries, remain insufficiently documented. Objectives: This study aims to (1) present the clinical characteristics of patients undergoing PRFR at a national tertiary brain center, and (2) identify clinical variables that predict optimal surgical outcomes. Methods: This prospective cohort study included 37 surgery-naïve and post-MVD recurrent TN patients who underwent PRFR between 2014 and 2020. Patient characteristics and offending pathologies were documented. Postoperative outcomes were assessed using the Barrow Neurological Institute (BNI) scales and the Numerical Rating Scale (NRS). Univariate and bivariate analyses were utilized to construct prediction models. Results: The cohort had a mean age of 59 ± 15 years. Among the patients, 51.4% were surgery-naïve, while 48.6% had a history of previous MVD. The PRFR procedure yielded significant NRS improvements in both the surgery-naïve (p < 0.001) and post-MVD (p = 0.001) groups, with no statistically significant difference in pain reduction between the two (p = 0.151). Preoperative identification of the offending pathology was a significant predictor of surgical success (p = 0.019), with small artery compression showing the highest rate of satisfactory outcomes. Conclusion: PRFR provides profound and immediate pain relief for both surgery-naïve patients and those with post-MVD recurrences. The nature of the offending pathology serves as a crucial clinical predictor for achieving optimal outcomes, making PRFR a highly reliable and cost-effective therapeutic pillar in the management of refractory TN.